Measurement of Vein Diameter for Peripherally Inserted Central Catheter (PICC) Insertion. Issue 5 (September 2015) - Sharp, Rebecca; Cummings, Melita; Childs, Jessie; Fielder, Andrea; Mikocka-Walus, Antonina; Grech, Carol; Esterman, Adrian
<x xml:space="preserve">Abstract</x> Choosing an appropriately sized vein reduces the risk of venous thromboembolism associated with peripherally inserted central catheters. This observational study described the diameters of the brachial, basilic, and cephalic veins and determined the effect of patient factors on vein size. Ultrasound was used to measure the veins of 176 participants. Vein diameter was similar in both arms regardless of hand dominance and side. Patient factors—including greater age, height, and weight, as well as male gender—were associated with increased vein diameter. The basilic vein tended to have the largest diameter statistically. However, this was the case in only 55% of patients.